Mineralogy of schists from the basement of the southwestern part of the Tazovsky peninsula of the West Siberian megabasin (Lenzitskaya oil exploration area, YNAD) - Ponomarev Vladimir Sergeevich; Ivanov Kirill Svaytoslavich; Khiller Vera Vital’evna (Федеральное государственное бюджетное образовательное учреждение высшего образования «Уральский государственный горный университет», 2019)
Relevance of the work. The crystalline basement of Western Siberia is a promising site in the search for oil and gas, but not a sufficiently studied subject. Promising rocks are granitoids and partly their metamorphic margins. Core samples from wells, which uncovered rocks of the basement of Western Siberia, are unique because they are rare and extremely difficult to access, so it is necessary to conduct a comprehensive detailed core study for geodynamic reconstructions and to consider the geological evolution of the region. Purpose of the work. The determination of the material composition of quartz-chlorite-mica schists from the pre-Jurassic basement of the northern (Arctic) part of the West Siberian megabasin uncovered by the Lenzitskaya well No 77 (depth is 3516–3502 m) 265 km east of Salekhard within the Yamalo-Nenets Autonomous District (YNAD). Results. The studied quartz-chlorite-mica schists are fine-grained rocks of a greenish-gray color; they have an interdigitation of thin beds of rock enriched in mica-quartz-carbonate substance (up to 2 mm thick) with a small amount of chlorite, and layers of quartz-chlorite-mica composition (up to 3 mm) with the presence of carbonate boudin. Intimate crumpling is often observed in the rock. In the lower part of the section (depth is 3516 m), the rocks have a medium-grained structure and are composed of calcite (60%), quartz (25%), mica (10%) and chlorite (5%). The quartz-sericiticchlorite-carbonate rock has a schistous form due to light layers of quartz-calcite composition with a thickness of up to 2 cm and thin layers of a chlorite-mica aggregate with a thickness of up to 2 mm. The following was established using X-ray electron probe microanalyzer CAMECA SX 100: muscovite, aluminoceladonite, quartz, chamosite, calcite, plagioclase, pumpellyite-(Fe2 +), rutile, fluorapatite, monazite, zircon, pyrite and chalcopyrite. Quartz-sericitic schists similar in composition were found by us in the basement rocks of the Priuralsky part of the West Siberian plate in the Shaimsk-Kuznetsovsk megaanticlinorium. Conclusion. The mineralogy of quartz-chlorite-mica schists from the pre-Jurassic basement of the northern part of the West Siberian megabasin (Lenzitskaya 77 well, depth is 3502–3516 m) was first described. It was established that the formation of quartz-chlorite-mica schists took place under the conditions of the upper prehnite-pumpellyite facie of metamorphism along the sedimentary substance. Later the rocks underwent changes in the process of propitilization.
Keywords: quartz-chlorite-mica schists; mineralogy; metamorphism; basement; West Siberian megabasin; YNAD; кварц-хлорит-слюдистые сланцы; минералогия; метаморфизм; фундамент; Западно-Сибирский мегабассейн; ЯНАО; 549+552.44(571.121)